4 целых 5/7-(x-6 целых 3/7)=2 целых 6/7

  • 4 5/7 - (х - 6 3/7)=2 6/7
    преобразуем целую часть:
    4 5/7 = 28+5=33/7(т.к 28=7*4)
    6 3/7 = 42+3=45/7(т.к 42=6*7)
    2 6/7 = 14+6=20/7 (т.к 14=2*7)
    33/7 - (х - 45/7)=20/7
    раскроем скобки:
    33/7 - х + 45/7=20/7
    группируем:
    - х = 20/7 - 33/7 - 45/7
    х = - 20/7 + 33/7 + 45/7
    решим:

    числитель:      - 20 + 33 + 45           58            2
    х      = -------------------------------------= -------- =  8 -------
    знаменатель:             7                     7          7

  • 4целых5/7-(х-6целых3/7)=2целых6/7
    х-6целых3/7=4целых5/7-2целых6/7
    х-6целых3/7=1целых6/7
    х=6целых3/7+1целых6/7
    х=8целых2/7
    Ответ:8целых2/7
    Удачи!